2007
DOI: 10.1111/j.1365-2036.2007.03561.x
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of and risk factors for erosive oesophagitis and non‐erosive reflux disease: a nationwide multicentre prospective study in Korea

Abstract: SUMMARY BackgroundProspective nationwide multicentre studies that have evaluated endoscopic findings and reflux symptoms using a well-designed questionnaire are very rare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
145
12
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(182 citation statements)
references
References 56 publications
23
145
12
2
Order By: Relevance
“…21 In contrast, NERD is more common in women. 2,7,15,16,34,39 A quantitative analysis of esophageal symptoms has showed that the symptom frequency and severity were significantly higher in women than in men. 8,36 On the other hand, the grade of esophagitis by esophagogastroduodenoscopy and the time period at pH below 4 during ambulatory 24-hour esophageal pH monitoring did not show any significant differences between men and women.…”
Section: Endoscopy-based Studymentioning
confidence: 99%
See 1 more Smart Citation
“…21 In contrast, NERD is more common in women. 2,7,15,16,34,39 A quantitative analysis of esophageal symptoms has showed that the symptom frequency and severity were significantly higher in women than in men. 8,36 On the other hand, the grade of esophagitis by esophagogastroduodenoscopy and the time period at pH below 4 during ambulatory 24-hour esophageal pH monitoring did not show any significant differences between men and women.…”
Section: Endoscopy-based Studymentioning
confidence: 99%
“…2 Similarly, a study with 10 837 healthy Japanese adults (6332 men and 4505 women, aged 20-87 years) who received gastroesophagoduodenoscopy has revealed that men, older age, alcohol, smoking, no H. pylori infection, higher pepsinogen I/II ratio in serum, and higher BMI were positively associated with reflux esophagitis. 36 In contrast, women, younger age, smoking, alcohol, H. pylori infection, higher pepsinogen I/II ratio in serum, and higher BMI were positively associated with NERD.…”
mentioning
confidence: 99%
“…In addition, many possible GERD patients, who are commonly encountered in one-third to one-half of the Korean population with GERD symptoms, were enrolled. 29 Hence, this study can reflect the actual aspects of the racial, geographic, and cultural specificities in Korean patients with GERD symptoms. Interestingly, most symptom-inducing foods are Korean traditional foods which have been consumed since a long time ago.…”
Section: Discussionmentioning
confidence: 97%
“…1 40개의 건강검진센터에서 25,536명을 대상으로 조 사한 연구에서 역류성 식도염의 유병률은 8%, 비미란성 역류질 환의 유병률은 4%였다. 2 국가차원의 암 검진 사업이 활발히 진행되고 있는 우리나라 에서는 무증상 성인이 건강검진목적의 내시경을 받는 경우가 많다. 이 과정에서 하부식도의 점막상해(mucosal break)가 발 견되어 역류성 식도염으로 진단받는 수진자가 많지만, 뚜렷한 증상이 없기 때문에 어떠한 치료 전략이 적용되어야 하는지 명 확하지 않다.…”
Section: 서 론unclassified